2015
DOI: 10.1007/s00268-014-2917-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between SMAD3 Expression and Preoperative Fluoropyrimidine‐Based Chemoradiotherapy Response in Locally Advanced Rectal Cancer Patients

Abstract: Our data suggested that analyzing pre-chemoradiotherapy tumors for phosphorylated SMAD3 overexpression would assist physicians in identifying locally advanced rectal cancer patients who may have a poor response risk to preoperative fluoropyrimidine-based chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…The finding of 3 independent SNPs predictive of pCR in SMAD3 provides a strong rational to an involvement of this gene in the response to CRT. Consistently with our data, the overexpression of phosphorylated SMAD3 in pre-CRT cancer tissues, was a marker of poor pathological response to fluoropyrimidines-based neoadjuvant CRT in 86 LARC patients [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…The finding of 3 independent SNPs predictive of pCR in SMAD3 provides a strong rational to an involvement of this gene in the response to CRT. Consistently with our data, the overexpression of phosphorylated SMAD3 in pre-CRT cancer tissues, was a marker of poor pathological response to fluoropyrimidines-based neoadjuvant CRT in 86 LARC patients [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…1 E, F). Treatment response to neoadjuvant CCRT is an early indicator of the long-term prognosis in LARC patients [ 23 , 24 ]. In the CAO/ARO/AIO-94 trial, patients with complete (TRG 4) or intermediate pathologic responses (TRG 2 and 3) had improved DFS after preoperative CCRT than those with poor responses [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…88 The phosphorylated isoform of SMAD3 is considered as a hallmark for SMAD3 activation, increased expression of which has been shown to be associated with a poor TRG. 60 b-Catenin can be detected at the membranous, cytoplasmic, and nuclear levels, representing its function within the Wnt cascade, and counts activation of genes linked to the APC gene among its downstream effects. A shift in treatment response has been demonstrated that is dependent on nuclear versus cytoplasmic expression of b-catenin, with increased nuclear expression being association with radioresistance.…”
Section: Cell Signalingmentioning
confidence: 99%
“…Nucleic acid metabolism p-SMAD3, 60 found that the greatest numbers of significant biomarkers lie in the domains of "response to stimulus" and the interplay of this domain with "cell death." In addition, while a relatively small number of biomarkers responsible for cellular metabolism have been evaluated to date, many of these demonstrate a high level of correlation with TRG.…”
mentioning
confidence: 99%
See 1 more Smart Citation